Palynological characteristics of Iabang lake sediments - Thuy Duong, Nguyen; Tung, Dang Xuan; Min, Nguyen Thi; Ha, Vu Van; Tuan, Dang Minh; Quang, Nguyen Minh; Dinh Thai, Nguyen (VNU Journal of Science: Earth and Environmental Sciences, 2025)
This paper presents the first pollen and spore record in lake sediment from the Tay Nguyen area, Vietnam, spanning the last 22.5 cal kyr BP. The analysis of spores and pollen from a core sample taken at a depth of 17.7 meters in Iabang Lake, Dak Doa District, Gia Lai Province, allows for the reconstruction of paleoclimate conditions over the past 22.5 cal Kyr BP. The climate conditions in the Iabang Lake area have changed from temperate to subtropical and then to tropical conditions. Findings compare favorably with other regional paleoclimate data. The record of spores and pollen in the lake sediments also indicates a period of dry and cold conditions interspersed with subtropical climate at about 17.1 to 16.1 cal kyr BP, which corresponds to the Heinrich 1 event.